Norms and Values in Japanese Democracy Assistance towards Southeast Asia Countries, 2008 – 2013 - Ishaq Rahman (Journal of Society and Governance, 2017)
Japan has a unique way in interpreting its involvement in global movement of democratization.  Although Japan boosts an adequate experience in transition to democracy after World War II as well as the economic prowess, Japan’s participation in democratization internationally has been very low for more than 50 years.  The Japanese involvement in democracy assistance around the world can be considered minor compared to other donor countries, especially among the OECD DAC members.  In relation with regional priority, Japanese ODA consistently place Southeast Asia as the main target for development assistance but with lesser compliance with supporting governance and civil society known as the core component of democracy assistance.  While Japan has adopted new foreign policy strategy known as the “Arc of Freedom and Prosperity”, including Southeast Asia region, there still remains a need and opportunity to increase Japan’s engagement in democratization process, either by promoting or protecting democracy.Keywords: Democracy Assistance, Governance, Southeast Asia.